Distributed Instructional Leadership in High Schools. Issue 2 (March 2013) - Halverson, Richard; Clifford, Matthew
This article explores the idea of distributed instructional leadership as a way to understand instructional leadership practice in comprehensive high schools. Our argument is that distributed leadership analyses allow researchers to uncover and explain how instructional improvement in high schools occurs through the efforts of multiple individuals working to simultaneously influence the contexts of leadership and the contexts of instruction. The distributed instructional leadership model draws on the full potential of distributed leadership to describe not only who is involved with high school reforms but also what situated tools, tasks, and routines are required to change and maintain improved teaching. The first part of the article develops an account of distributed instructional leadership as an approach to studying how leaders create high school learning environments, by drawing on research in distributed cognition. The second part provides an illustration of how the ideas of distributed instructional leadership were applied to the analysis of a curriculum-based reform in a comprehensive high school.